Perception on airline e-ticketing: a study among lecturers at UiTM Kampus Bandaraya Melaka / Muhammad Shafiqal Abdullah Saidi and Muhammad Izzat Muhammad Rusiyadi - Abdullah Saidi, Muhammad Shafiqal; Muhammad Rusiyadi, Muhammad Izzat (Faculty of Administrative Science and Policy Studies, 2013)
The “airline e-ticketing” has been implementing by many airline company in order to generate more income and give facilities to their customer. The perception from lectures in UiTM Kampus Bandaraya Melaka has given opportunity to understand the perception by an academician about the airline e-ticketing. This study examines the Lectures perception towards airline e-ticketing. The total of sampling is over 100 respondents done at UiTM Kampus Bandaraya Melaka. The web security, customer confident and usefulness are the factor that may influence the perception on airlines e-ticketing by the lectures in UiTM Kampus Bandaraya Melaka. The most influence factor towards the perception on airline e-ticketing by the lectures in UiTM Kampus Bandaraya Melaka is the usefulness.